Among the Two Kinds of Metacognitive Evaluation, Only One Is Predictive of Illusory Object Perception. (October 2020) - Vetik, Sandra; Tulver, Kadi; Lints, Diana; Bachmann, Talis
The relationship between expectation-induced hallucination proneness and self-confidence in performance was studied in a visual perception task. Participants were prompted either to recognize briefly shown faces as male or female or to rate the subjective vividness of a square surrounding the face. Importantly, in a few critical trials, the square was absent. Upon completion, participants rated their performance in the face recognition task; they were also asked whether they were sure that their estimation was correct. Out of 35 participants, 33 "hallucinated" on at least one trial, rating the square as visible when it was actually absent. Negative correlation between hallucination proneness and self-confidence in performance (metacognitive rating) was found: The more hallucinations a participant experienced, the less confident he/she was in his/her performance in the face recognition task. Most subjects underestimated their performance; higher ratings were also more accurate. Thus, higher hallucination proneness was associated with more inaccurate ratings of one's own perception. However, confidence in self-ratings as measured by the second follow-up question was unrelated to both, hallucination proneness and self-confidence in performance, supporting the view that there is no unitary mechanism of metacognitive evaluations and extending this view to the domain of visual hallucinatory perception.